Out of balance - postural control in cancer patients before and after neurotoxic chemotherapy - Müller, Jana; Ringhof, Steffen; Vollmer, Maxmilian; Jäger, Laura Bettina; Stein, Thorsten; Weiler, Markus; Wiskemann, Joachim (Gait & posture, 2020)
Background - Chemotherapy-induced peripheral neuropathy (CIPN) is a serious side effect deriving from neurotoxic chemotherapeutic agents. The underlying nerve injury can affect proprioception causing impaired postural control, gait difficulties and a higher risk of falling. Overall, the symptoms and functional limitations negatively affect patients’ independence and quality of life. - Research question - Our objective was to analyze postural control in cancer patients before and after neurotoxic chemotherapy and to compare these data to healthy controls. - Methods - Participants were 35 cancer patients (PAT) and 35 healthy, one-to-one gender, age, height, and weight matched controls (HMC). Postural control of HMC was tested once, whereas PAT were tested prior to (PATpre) and three weeks after completion of neurotoxic chemotherapy (PATpost). Temporal, spatial and frequency domain measures of the center of pressure (COP) were calculated using a force plate. The following balance conditions were analyzed: bipedal stance with open (BPEO) and closed eyes (BPEC), semi-tandem (STEO, STEC) and monopedal stance (MPEO). CIPN was assessed clinically (Total Neuropathy Score) and via questionnaire. Time and group differences were determined by using Wilcoxon-signed-rank tests. Spearman correlation was applied to analyze associations between severity of CIPN and postural control. - Results - PATpost showed significantly increased temporal and spatial measures of the COP (p<.05) - both after neurotoxic chemotherapy (PATpre-PATpost) and in comparison to HMC. Withdrawal of visual control resulted in greater temporal and spatial COP displacements in PATpost than in the comparative groups (PATpre, HMC). Correlation analyzes revealed moderate associations of COP measures with clinical CIPN measures and low to none for the questionnaires. - Significance - Three weeks after completion of neurotoxic chemotherapy, PATpost showed significant balance deficits compared to PATpre and HMC. Especially the deficits in the standing conditions with closed eyes may indicate an impaired proprioception. This hypothesis is supported by the finding that stronger CIPN symptoms were associated with poorer postural control. However, future studies need to take further influencing factors on postural control into account (e.g. strength) in order to generate efficacious rehabilitation measures.
Gesehen am 14.04.2020